Jungle of bones - Mikaelsen, Ben, 1952- (Scholastic Press, 2014)
When sullen teenager Dylan Barstow is caught joyriding in a stolen car he is sent to his ex-Marine uncle for the summer, but soon they are on the way to Papua New Guinea in search of a World War II fighter plane and Dylan discovers that defiance is not a survival skill when you are lost in a jungle.